Perempuan Minang Merantau - Wenhendri Wenhendri; Yusril Yusril; Ediwar Ediwar (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
AbstractDesigning theatrical work of female migration scripts, inspired by the phenomenon of social change in the Minangkabau community, which tells the story of minangkabau women who go abroad. Social change has and will continue to occur, it may occur as a development from whitin society itself. So every Minangkabau person must know the kinship arrangement with each other other, in order to understand his own place and position. Exploring the value of tradition and preserving the noble values of the nation are the main ideas that will be poured in this work, namely modern theater that cannot be separated from the text elements of a literary work in a complete composition, dialogs, moods, spectacles, backgrounds, themes and figures that bintolakan randai. Randai pattern is meant here, the motion, dialogue, gurindam, character and story. In the creation of theater art, writers and directors do randai pattern as traditional theater Minangkabau mate with the nature of modern theater, in which the players in the women’s migration script must be clever, shrewd, silat, ekting and dialogue.Keywords : Theater Migration of Women is a Modern TheaterAbstrakPerancangan karya seni teater naskah lakon Migrasi Perempuan, terinspirasi dari fenomena perubahan sosial masyarakat Minangkabau, yang bercerita tentang perempuan Minangkabau yang pergi merantau. Perobahan sosial telah dan akan terus terjadi, mungkin terjadi sebagai perkembangan dari dalam masyarakat itu sendiri. Maka setiap orang Minangkabau wajib mengetahui susunan kekerabatan satu dengan yang lainnya, supaya dapat memahami tempat dan kedudukannya sendiri. Menggali nilai tradisi dan melestarikan nilai-nilai luhur bangsa adalah gagasan utama yang akan dituangkan dalam kekaryaan ini, yaitu teater modern yang tidak terlepas dari unsur-unsur teks suatu karya sastra dalam susunan yang utuh; (dialog, mood, spektakel, latar, tema dan tokoh) yang berpolakan randai. Pola-pola randai yang dimaksud disini adalah, adanya gerak, dialog, gurindam, penokohan dan cerita. Dalam penciptaan karya seni teater, penulis sekaligsus sutradara melakukan pola-pola randai sebagai teater tradisional Minangkabau mengawinkan dengan hakekat teater modern, yang mana para pemain dalam naskah lakon Migrasi Perempuan harus pandai berdendang, bergore, gerak silat, akting dan dialog.Kata kunci : Teater “Perempuan Minang Merantau”, randai, teater, modern